2021
DOI: 10.33192/smj.2021.75
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Postoperative Colorectal Cancer Survivors: A Structural Equation Model

Abstract: Objective: The present study has been aimed at constructing a causal model to determine factors affecting healthrelatedquality of life (HRQoL) in postoperative patients with colorectal cancer (CRC) following discharge.Materials and Methods: A cross-sectional study was conducted with 396 postoperative CRC cancer patients fromten tertiary hospitals representing each of the four Regions of Thailand. Data was collected through a standardquestionnaire. Structure equation modeling (SEM) was applied to analyze data.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…These results are consistent with the prior studies in other countries, which found that marital status, sexual activity and healthcare provider support were significantly associated with QOL in CRC ostomates (Alenezi et al, 2021;Andrade et al, 2016). However, the family care levels were prominently reported with a strong relation to QOL in Thai CRC ostomates and differed from those in other countries (Atthaphinan & Lueboonthavatchai, 2017;Decha & Navicharern, 2016;Janthathai et al, 2018;Suttipong et al, 2021;Teerathongdee, 2014). It reflects that QOL in Thai CRC ostomates was influenced by the levels of care from the family where they lived as an extended family.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These results are consistent with the prior studies in other countries, which found that marital status, sexual activity and healthcare provider support were significantly associated with QOL in CRC ostomates (Alenezi et al, 2021;Andrade et al, 2016). However, the family care levels were prominently reported with a strong relation to QOL in Thai CRC ostomates and differed from those in other countries (Atthaphinan & Lueboonthavatchai, 2017;Decha & Navicharern, 2016;Janthathai et al, 2018;Suttipong et al, 2021;Teerathongdee, 2014). It reflects that QOL in Thai CRC ostomates was influenced by the levels of care from the family where they lived as an extended family.…”
Section: Discussionsupporting
confidence: 88%
“…Themes were drawn from the abstraction and synthesis procedure, The relationships between QOL and sociodemographic and clinical variables, such as personal characteristics and illness history, had been studied to understand the influence of these variables on QOL in Thai CRC ostomates. Six quantitative studies tested the associations between sociodemographic and clinical variables and QOL (Atthaphinan & Lueboonthavatchai, 2017;Chutikamo et al, 2017;Decha & Navicharern, 2016;Janthathai et al, 2018;Maneesin et al, 2012;Suttipong et al, 2021).…”
Section: Themesmentioning
confidence: 99%
See 3 more Smart Citations